Solvation Structure Design for Aqueous Zn Metal Batteries - Cao, Longsheng; Li, Dan; Hu, Enyuan; Xu, Jijian; Deng, Tao; Ma, Lin; Wang, Yi; Yang, Xiao-Qing; Wang, Chunsheng (Journal of the American Chemical Society, 2020)
Aqueous Zn batteries are promising energy storage devices for large-scale energy-storage due to low cost and high energy density. However, their lifespan is limited by the water decomposition and Zn dendrite growth. Here, we suppress water reduction and Zn dendrite growth in dilute aqueous electrolyte by adding dimethyl sulfoxide (DMSO) into ZnCl2–H2O, in which DMSO replaces the H2O in Zn2+ solvation sheath due to a higher Gutmann donor number (29.8) of DMSO than that (18) of H2O. The preferential solvation of DMSO with Zn2+ and strong H2O–DMSO interaction inhibit the decomposition of solvated H2O. In addition, the decomposition of solvated DMSO forms Zn12(SO4)3Cl3(OH)15·5H2O, ZnSO3, and ZnS enriched-solid electrolyte interphase (SEI) preventing Zn dendrite and further suppressing water decomposition. The ZnCl2–H2O–DMSO electrolyte enables Zn anodes in Zn||Ti half-cell to achieve a high average Coulombic efficiency of 99.5% for 400 cycles (400 h), and the Zn||MnO2 full cell with a low capacity ratio of Zn:MnO2 at 2:1 to deliver a high energy density of 212 Wh/kg (based on both cathode and anode) and maitain 95.3% of the capacity over 500 cycles at 8 C.